Fungal spores as a source of sodium salt particles in the Amazon basin. Issue 1 (December 2018) - China, Swarup; Burrows, Susannah; Wang, Bingbing; Harder, Tristan; Weis, Johannes; Tanarhte, Meryem; Rizzo, Luciana; Brito, Joel; Cirino, Glauber; Ma, Po-Lun; Cliff, John; Artaxo, Paulo; et al.
Abstract In the Amazon basin, particles containing mixed sodium salts are routinely observed and are attributed to marine aerosols transported from the Atlantic Ocean. Using chemical imaging analysis, we show that, during the wet season, fungal spores emitted by the forest biosphere contribute at least 30% (by number) to sodium salt particles in the central Amazon basin. Hydration experiments indicate that sodium content in fungal spores governs their growth factors. Modeling results suggest that fungal spores account for 69% (31–95%) of the total sodium mass during the wet season and that their fractional contribution increases during nighttime. Contrary to common assumptions that sodium-containing aerosols originate primarily from marine sources, our results suggest that locally-emitted fungal spores contribute substantially to the number and mass of coarse particles containing sodium. Hence, their role in cloud formation and contribution to salt cycles and the terrestrial ecosystem in the Amazon basin warrant further consideration. Salt particles in the Amazon basin are typically attributed to marine aerosols transported from the Atlantic Ocean. Here the authors show the potential importance of fungal spores as a source of sodium-salt particles in the Amazon rainforest.